Relationship between Soluble Fms-Like Tyrosine Kinase-1 (Sflt-1) Levels in Preeclamptic Mothers with Asphyxia - Wahida Wahida; Gusriani Gusriani (Majalah Kesehatan Indonesia, 2023)
Soluble Fms like tyrosine kinase 1 (sFlt-1) is one of the markers that play a role in the pathogenesis of pregnancy-induced hypertension. The research aimed to determine the relationship between sFlt-1 level and asphyxia. The samples were preeclampsia inpartu consisting of 22 people, and normal pregnancy women consisting of 18 people. An analytic observational study with cross-sectional was conducted. The level of sFlt-1 was examined using ELISA. Statistic analysis used Kruskal Wallis test, One-way Anova test and Pearson correlation test.  The results showed the facts of the study in the preeclampsia and control groups were not different (p> 0.05). In the preeclampsia group, and the control group (7.876 ± 3.792 ng / mL; p <0.05). There was a difference between sFlt-1 levels and the incidence of asphyxia (p = 0.003) in the preeclampsia group, whereas in the control group no relationship was found between sFlt-1 levels and asphyxia (p> 0.05).